Purification‐Free, Small‐Scale Synthesis of Isothiocyanates by Reagentless Fragmentation of Polymer‐Supported 1, 4, 2‐Oxathiazoles. Issue 5 (5th December 2013) - Burkett, Brendan A.; Fu, Pincheng; Hewitt, Russell J.; Ng, Su Ling; Toh, Joel D. W.
Abstract: The synthesis of isothiocyanates (ITCs) by employing polymer‐supported 1, 4, 2‐oxathiazoles is described. The ITCs are obtained in moderate yields and high purity through a reagentless, thermal fragmentation of polymer‐supported 1, 4, 2‐oxathiazoles that are obtained by trapping nitrile oxides with polymer‐supported thiocarbonates. Abstract : A purification‐free, small‐scale synthesis for isothiocyanates (ITCs) is reported that proceeds through a catch‐and‐release system. This is a convenient method to produce small quantities of ITCs in high purity for screening purposes.